Hyperinsulinemia Induced Altered Insulin Signaling Pathway in Muscle of High Fat- and Carbohydrate-Fed Rats: Effect of Exercise. (24th February 2021) - Joseph, Anu; Parvathy, S.; Varma, Koyikkal Karthikeya
Abstract : Insulin resistance is a state of impaired responsiveness to insulin action. This condition not only results in deficient glucose uptake but increases the risk for cardiovascular diseases (CVD), stroke, and obesity. The present work investigates the molecular mechanisms of high carbohydrate and fat diet in inducing prediabetic hyperinsulinemia and effect of exercise on InsR signaling events, muscular AChE, and lactate dehydrogenase activity. Adult male Wistar rats were divided into the control (C) diet group, high-carbohydrate diet (HCD) group, high-fat diet (HFD) group, and HCD and HFD groups with exercise (HCD Ex and HFD Ex, respectively). Acetyl choline esterase activity, lactate dehydrogenase activity, total lactate levels, IRS1 phosphorylations, and Glut4 expression patterns were studied in the muscle tissue among these groups. High carbohydrate and fat feeding led to hyperinsulinemic status with reduced acetylcholine esterase (AChE) activity and impaired phosphorylation of IRS1 along with increased lactate concentrations in the muscle. Exercise significantly upregulated phosphoinositide 3 kinase (PI3K) docking site phosphorylation and downregulated the negative IRS1 phosphorylations thereby increasing the glucose transporter (GLUT) expressions and reducing the lactate accumulation. Also, the levels of second messengers like IP3 and cAMP were increased with exercise. Increased second messenger levels induce calcium release thereby activating the downstream pathway promoting the translocation of GLUT4 to the plasma membrane. Our results showed that the metabolic and signaling pathway dysregulations seen during diet-induced hyperinsulinemia, a metabolic condition seen during the early stages in the development of prediabetes, were improved with vigorous physical exercise. Thus, exercise can be considered as an excellent management approach over drug therapy for diabetes and its complications.